PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA KELAS X SMA NEGERI 1 KUPANG - Tae, Lidwina Felisima; Fakhruddin, Fakhruddin; Soko, Imelda Paulina; Prakoso, Bagus Hary (Pusat Asesmen dan Pembelajaran, 2019)
Two Stay Two Stray is a cooperative learning model which is majoring the cooperation of each member of group to finish the task given and give chance to its member to share information each other with another group member by following a certain pattern. The purpose of this research is to investigate the difference of learning achievement between students who have been taught using cooperative learning model of Two Stay Two Stray type with three intersection pattern and students who have been taught using cooperative learning model of Two Stay Two Stray type with the simple pattern. The participants of this research are two groups of 10th grader, the A class as the experiment group and the B class as the control group respectively. The instruments used in this research is Two Stay Two Stray with three intersection pattern and simple pattern learning which is manifested in the syllabus, Teaching Implementation Plan (RPP), and the questions for pre test and post test. The results of the data analysis were: 1) There was a difference in achievement between students who have been taught using cooperative learning of Two Stay Two Stray type with three intersection pattern and students who have taught using a model of cooperative learning by Two Stay Two Stray type with simple pattern, 2) the learning achievements of students who have taught using cooperative learning model of Two Stay Two Stray type with three intersection pattern were higher than students who have taught using cooperative learning model of Two Stay Two Stray type with simple pattern.